Characterization of Polydimethylsiloxane Dielectric Films for Capacitive ECG Bioelectrodes - Alhassan Haruna Umar; Fauzan Khairi Che Harun; Yusmeeraz Yusof (IAES Indonesia Section, 2020)
Capacitive ECG bioelectrodes are potentials for wearable and long-term physiological monitoring applications. In non-contact ECG recordings, the dielectric material sets limit to smooth bioelectric signal acquisition. Previously used dielectrics are rigid, unconformable on the skin, induce artefact and triboelectric noise, and becomes unstable when they absorb skin exudates. Recently, polymeric materials such as PDMS have gained different biomedical applications because it is biocompatible, flexible, and easy to fabricate. However, its use as a dielectric for capacitive ECG sensing is poorly reported. In this study, 15 samples of thin PDMS films of various thicknesses were fabricated by varying the proportion of the Sylgard 184TM silicone elastomer to the crosslinker from Dow Corning Corporation and manually deposited on acrylic glass substrates. The composition ratio and thickness were used to tune the structure and dielectric properties of the films. The effects on the capacitance generated by each dielectric film were measured using the parallel plate method, and their corresponding values of relative permittivity was also estimated. The results obtained reveal that PDMS films made from a composition ratio of 10:2 yielded the maximum capacitance and relative permittivity. In contrast, the film with 0.14mm thickness revealed the highest value of capacitance (31pF). The recorded values of capacitance demonstrate the feasibility of PDMS dielectrics for capacitive ECG bioelectrodes.